The Effect Of Local Wisdom-Based Project Learning Model On Character And Outcomes Of grade iv students - Sartika Sartika; Mulyadi Mulyadi; Erwin Nurdiansyah (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2026)
Study This aim For know the influence of learning models project based wisdom local to character and results Study Mathematics student class IV of State Elementary School 80 Kuri Lompo. In general specific, research This examine: 1) influence partial learning model to character students, 2) influence partial to results Study Mathematics, and 3) influence simultaneous to character and results Study Mathematics. Research use approach quantitative with type survey. A sample of 23 students taken total sampling. Data collected through observation, tests, questionnaires, and documentation, then analyzed using validity and reliability tests, as well as analysis statistics descriptive and inferential (t-test, regression, F-test, and coefficient determination) with SPSS assistance. Research results show implementation of Project Based Learning (PjBL) based on wisdom local implemented with good and impactful positive. Learning model This increase activeness, collaboration, independence, and character positive student like not quite enough answer, work equality, honesty, discipline, and independence. In addition, PjBL proven effective increase understanding draft number count, with an average value increase from 76.39 to 87.26 and the percentage completeness increase from 65% to 87%. Analysis inferential show influence significant this model to character and results Study in a way partial and simultaneous, affirming effectiveness PjBL based wisdom local in increase performance academic and character student.